Performance comparison of executing fast transactions in bitcoin network using verifiable code execution - Singh P.; Chandavarkar B.R.; Arora S.; Agrawal N. (My University, 2025)
In this paper, we study Bitcoin network for electronic cash transactions, and compare the extension to the BTCs network which inculcates provision of executing fast transactions with greater security and assurance with the former method of Proof-Of-Work for executing transactions. Above milestones are achieved by introducing the concepts of mutual trust and verifiable code execution between the payer and the payee in the network. Our work proposes a significant modification of the Pioneer model to provide a two-party trust framework for Bitcoin transactions; considerably faster compared to the generic trust platform of Bitcoin networks based on slow proof-of-work. The scheme proposed can promote the use of Bitcoin transactions in real life scenarios, where fast transactions are desirable due time constraints between the payment and the service. © 2013 IEEE.